Pengaruh Penggunaan Permainan Edukatif Maze Angka Terhadap Mengembangkan Kecerdasan Logika Matematika Anak Usia 5-6 Tahun - Nabila Dwirizki Handayani; Ahmad Syukri Sitorus (Jurnal Raudhah, 2026)
This study aims to analyze the effect of using the number maze educational game tool (APE) on the development of mathematical logic intelligence in children aged 5-6 years at Nurul Ilmi IT Kindergarten. The main problem underlying this research is the low ability of children to recognize number symbols and solve simple numerical problems due to unvaried learning methods. The research method used is quantitative with a quasi-experimental design of the One-Group Pretes-Postes type. The research sample consisted of 15 children selected using a purposive sampling technique. Data were collected through structured observation sheets and analyzed using paired sample t-test. The results showed that the application of the number maze game had a significant effect on improving children's mathematical logic intelligence. This can be seen from the drastic increase in the average score of children's abilities after being given the intervention. This study recommends the use of number maze media as an effective alternative learning media to stimulate logical-mathematical thinking skills in early childhood education institutions.